(untitled) - Goldsby, Richard A. (New York, 2000)
Amherst College, MA. Immunology textbook for students. Previous edition, c1997, was titled Immunology, by Janis Kuby. Presents a current and comprehensive introduction to the principles and research in the field. Color highlighting and illustrations. DNLM: Immune System--immunology.
Keywords: Immune System,Hệ miễn dịch,Immunology,Miễn dịch học; Immunology,Miễn dịch học